2017
DOI: 10.1097/pcc.0000000000001183
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers for Early Acute Kidney Injury Diagnosis and Severity Prediction: A Pilot Multicenter Canadian Study of Children Admitted to the ICU

Abstract: Objective Acute kidney injury (AKI) occurs early in pediatric intensive care unit (PICU) admission and increases risks for poor outcomes. We evaluated the feasibility of a multi-centre AKI biomarker urine collection protocol and measured diagnostic characteristics of urine neutrophil gelatinase-associated lipocalin (NGAL), interleukin-18 (IL-18) and liver fatty acid binding protein (LFABP) to predict AKI and prolonged AKI. Design: Prospective observational pilot cohort study. Setting: Four Canadian tertiar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Biomarkers have been explored as a way to detect kidney injury earlier than rising serum creatinine and to predict hospital outcomes in both adult and pediatric settings (33)(34)(35)(36)(37). These biomarkers are also being explored as possible markers of CKD and its progression (38).…”
Section: Cardiac Surgery Populationmentioning
confidence: 99%
“…Biomarkers have been explored as a way to detect kidney injury earlier than rising serum creatinine and to predict hospital outcomes in both adult and pediatric settings (33)(34)(35)(36)(37). These biomarkers are also being explored as possible markers of CKD and its progression (38).…”
Section: Cardiac Surgery Populationmentioning
confidence: 99%
“…Many authors investigating AKI causes have noticed that in 50–80% of the cases, the cause of AKI is not a renal disease, but other disease (so-called secondary AKI), and such AKI develops as a consequence of the main disease [2,5,9]. Comparison of PICU-treated children who developed AKI with those who did not develop AKI revealed no significant difference in the distribution of patients by diagnosis between the groups [23]. Our study also showed that in all cases (100%), the cause of AKI was not a renal disease and there was no significant association between diagnosis and AKI development.…”
Section: Discussionmentioning
confidence: 99%
“…In 2015, the study by McCaffrey et al reported that uNGAL level directly correlated with AKI [1]. However, there are studies reporting no significant difference in the NGAL comparing patients who developed AKI and did not develop AKI [23]. This confirms the necessity to continue more studies on uNGAL of children admitted in PICU.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were recruited from the respective cohorts of two older studies, from which the first compared cystatin C with serum creatinine in critically ill children [ 49 ]. The second trial was also performed in pediatric ICU patients; it aimed to compare certain biomarkers for early AKI diagnosis and grading [ 50 ]. The initial urine samples were collected within a maximum of three days after ICU admission; afterwards, samples were stored daily until days 5 or 14.…”
Section: Acute Kidney Injurymentioning
confidence: 99%